2007
DOI: 10.1295/polymj.pj2006193
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of Polymers onto Carbon Microcoil by Use of Carboxyl Groups on the Surface and Electric Properties of Conductive Composite Prepared from Silicone Rubber with the Polymer-Grafted Carbon Microcoil

Abstract: ABSTRACT:Carboxyl groups were successfully introduced on carbon microcoil (CMC) surface by the treatment with nitric acid. The carboxyl group content increased with increasing reaction time and reached to 1.34 mmol/g after 10 h. Poly(ethylene glycol) (PEG) was grafted onto the CMC surface by the reaction of carboxyl groups with terminal hydroxyl groups of PEG in the presence of condensing agent such as N,N 0 -dicyclohexylcarbodiimide or Lewis acid catalyst such as scandium (III) trifluoromethanesulfonate. Carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Then the amount of oxides as COOH groups calculated from the weight loss was estimated as 1.1, 1.9, and 2 6 × 10 −3 mol/g for 7, 10, and 12 h treatments, respectively. From the titration measurement, it was reported that the amount of oxides was 1 34 × 10 −3 mol/g for CMC after nitric acid treatment of 10 h. 24 The present result is considerably consistent with the previous report. As compared to the related nanocarbon material, the amount of carboxyl groups for multiwalled carbon nanotube was 3 7 × 10 −3 mol/g after 48 h acid-treatment.…”
Section: Surface Functionalization Of Cmcsupporting
confidence: 93%
“…Then the amount of oxides as COOH groups calculated from the weight loss was estimated as 1.1, 1.9, and 2 6 × 10 −3 mol/g for 7, 10, and 12 h treatments, respectively. From the titration measurement, it was reported that the amount of oxides was 1 34 × 10 −3 mol/g for CMC after nitric acid treatment of 10 h. 24 The present result is considerably consistent with the previous report. As compared to the related nanocarbon material, the amount of carboxyl groups for multiwalled carbon nanotube was 3 7 × 10 −3 mol/g after 48 h acid-treatment.…”
Section: Surface Functionalization Of Cmcsupporting
confidence: 93%
“…Carboxyl group functionalized CMCs were prepared using nitric acid and then coated with poly(ethylene glycol) (PEG) or poly(isobutyl vinyl ether) (IBVE). The PEG-coated CMCs were dispersed in water and poly-IBVE-coated CMCs were well dispersed in silicone rubber [63]. Bi et al [64,65] demonstrated nickel-phosphorus (Ni-P) coating on the surface of double helical CMCs (Figure 23) using an electroless plating process to add magnetic properties.…”
Section: Functionalization Of Coiled Carbon Filamentsmentioning
confidence: 99%